Glucose-6 Phosphate Dehydrogenase Deficiency in terms of hemolysis indicators and management - Al-Momen, Hayder H.; Athab, Muthanna F.; Al-Zubaidi, Anwer S. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Glucose-6 Phosphate Dehydrogenase (G6PD) Deficiency is one of the commonest inherited enzyme abnormalities in humans, caused by many mutations that reduce the stability of the enzyme and its level as red cells progress in age. Objectives: To determine the useful hematologic indicators of hemolysis, observe an early detection of G6PD enzyme deficiency (if any), and the available therapeutic measures. Patients and Methods: 123 patients with G6PD deficiency and hemolysis after exposure to fava beans whom visited AL-Elwiya Pediatric Teaching Hospital from the 1st of February 2016 till 31st of May 2016 were entered this study retrospectively. Hemolysis laboratory indicators were observed. Management supportive measures were put in consideration also. Results: We found that 10-20% levels of hematocrit and normochromic normocytic anemia were the most frequent on presentation, while a range of 15.1-20% of reticulocyte counts was the most common with lower rates in females group. Hyperbilirubinemia was seen with nil patients had abnormal renal function tests. About three quarters (76.4%) of the total number of involved cases had glucose-6-phosphate dehydrogenase (G6PD) deficiency. Only 4 patients required no blood transfusion, 102 patients (82.9%) needed transfusion once, and the rest 17 (13.8%) had more than one blood transfusion. Most of cases (91.1%) recovered within the first 3 days. However; all cases were recovered by the fourth day of admission. Conclusion: Hemoglobin and blood morphology with hyperbilirubinemia were useful hematologic indicators of hemolytic process, while blood transfusion was the most used therapeutic measure, and recovery was expected within 2-3 days.